Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan di PT. Supreme Energy Muara Laboh (SEML) Kab. Solok Selatan Provinsi Sumatera Barat - M. Roza; Rijal Abdullah; Yunasril Yunasril (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Human resources are an important role for the success of an organization or company. Humans are living assets that need to be nurtured and developed. One of the things that should be a major concern for human resource managers is the occupational safety and health system. PT. Supreme Energy Muara Laboh is one of the geothermal companies that has been established since 11 years ago. This company is located in Muara Laboh, West Sumatra. The main problem that exists in this company is the occurrence of work accidents as many as 50 accidents experienced by employees during 2012-2015. Accidents that occur can disrupt  geothermal operational activities and endanger the safety of workers. Based on the description above, the author is interested in conducting research with the title "The Effect of Occupational Safety and Health on Employee Performance of PT. Supreme Energy Muara Laboh"Based on data processing for work safety program variables, the value of t-count is 3.388 which means that is greater than t-table which is 2.179, with a significance of 0.349 which is more than 0.05. It is mean that Ho1 is rejected , meaning that the work safety program has a significant influence on Employee Performance. Keywords:  Occupational Safety and Health, Employee performance, Work Accident,Occupational Safety Program, Geothermal